TEACHERS' VIEWS ON THE INTEGRATION OF TECHNOLOGY IN EFL CLASSROOM - Firima Zona Tanjung (IJIET (International Journal of Indonesian Education and Teaching), 2020)
In many study results, technology integration has been indicated to contribute regularly on the development of students’ 21st century skills ultimately in this digital era. This condition particularly creates new challenges for language teachers, e.g. being digitally literate, being adaptable with rapid technological changes, finding alternatives to stimulate the students to learn, and creating conducive class atmosphere. Considering previous points, this paper presents teachers’ views on the integration of technology in their EFL classroom. A qualitative method was utilized in which the data were in the form of comments dealing with technology use and teachers’ views on technology integration in their classroom. The compiled data were then analyzed by applying an interactive model. The findings showed that teachers have positive views on the integration of technology in EFL classroom. Stated benefits of technology integration on enabling the development of students’ 21st century skills, teachers are highly demanded to encourage students’ active participation by engaging them through meaningful learning activities and use of technology simultaneously. Therefore, teachers should put high attention on the process of selecting, preparing, integrating, assessing, and evaluating types of technology being employed in classroom instruction.